Complete Genome Sequence of Bacteriophage SEN8, a Temperate Phage Isolated from Salmonella enterica subsp. salamae - Bosák, Juraj; Mikalová, Lenka; Čejková, Darina; Šmarda, Jan; Šmajs, David (Genome announcements, 2017)
A temperate phage, SEN8, having a broad activity against pathogenic Salmonella serovars, was isolated from Salmonella enterica subsp. salamae strain Sen8. The complete genome sequence of phage SEN8 was determined (35,203 bp) and showed relatedness to P2-like phages (Salmonella phages Fels-2 and RE-2010).